Upaya Meningkatkan Keaktifan Belajar Siswa Materi Kerja Sama Dalam Berbagai Bidang Dengan Model Pembelajaran Kooperatif Make A Match Terhadap Hasil Belajar - Muhammad Sobirin; Welius Purbonuswanto (Jurnal Pendidikan Dasar, 2022)
Improving Activeness and Learning Outcomes of Applicable Norms in Social Life toRealize Justice through the Make A Match Type Cooperative Method for Class VIIB students ofSMP Negeri 1 Dukun in the 2021/2022 academic year. The purpose of this study was todetermine whether there was an increase in PPKn activity and learning outcomes for classVIIB students of SMP Negeri 1 Dukun in the 2021/2022 academic year by using the Make AMatch type of learning method. This research was carried out at SMP Negeri 1 Dukun in theacademic year 2021/2022 with the subjects of the study being class VIIB students consisting of14 male students and 14 female students. The method used in this classroom action researchconsists of two cycles. In the first cycle, learning was carried out using the Make A Matchcooperative method in large groups, each group consisting of 7 students, while in the secondcycle using the Make A Match cooperative method in small groups, each group consisting of 4students.Each cycle consists of four stages of research, namely planning, implementingactions, observing and reflecting. Comparative descriptive is done by comparing the data inthe initial conditions, cycle I, and cycle II, both on learning activity and learning outcomes.The results of the study show that: First, the use of the Make A Match type cooperative methodcan increase the learning activity of Cooperation Civics in various fields for class VIIBstudents of SMP Negeri 1 Dukun in the 2021/2022 academic year. It is proven that thepercentage of students in active learning increased from the initial condition of 54% to 83% inthe first cycle and to 93% in the second cycle or in the final condition, an increase of 39% fromthe initial condition. Second: the use of the Make A Match type of cooperative method canimprove Civics learning outcomes on Cooperation materials in various fields in class VIIB ofSMP Negeri 1 Dukun in the 2021/2022 academic year. It is proven that the percentage ofstudent learning completeness increased from the initial condition of 46% to 79% in the firstcycle and to 84% in the second cycle or an increase of 38% from the initial condition.